Expertise revisited, Part II: Contributory expertise. (April 2016) - Collins, Harry; Evans, Robert; Weinel, Martin
Abstract: In Part I of this two part paper we tried to elicit the 'essence' of the notion of interactional expertise by looking at its origins. In Part II we will look at the notion of contributory expertise. The exercise has been triggered by recent discussion of these concepts in this journal by Plaisance and Kennedy and by Goddiksen.